2014
DOI: 10.1007/s11695-014-1312-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Analysis of Single Incision vs Traditional Multiport Sleeve Gastrectomy: A Matched Cohort Study

Abstract: Sleeve gastrectomy can be performed safely using single incision techniques with equivalent outcomes for weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…After removing duplicates (n = 79), the 1554 records were screened by title and abstract after which 1179 were excluded and the full-text articles for the remaining 375 records were assessed for eligibility. A total of 148 papers were included in the final analysis and the number of studies per reinforcement method were: 69 for NO-SLR [9, 17-84], 70 for suture [9,19,20,22,26,30,46,51,53,75,76,78,83,, 9 for BPS [9,72,78,83,86,89,[141][142][143], 9 for Seal [9,30,61,74,78,103,[144][145][146], and 24 for APM [9,39,52,53,63,89,103,131,[147][148][149][150][151][152][153][154][155][156][157][158][159][160]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…After removing duplicates (n = 79), the 1554 records were screened by title and abstract after which 1179 were excluded and the full-text articles for the remaining 375 records were assessed for eligibility. A total of 148 papers were included in the final analysis and the number of studies per reinforcement method were: 69 for NO-SLR [9, 17-84], 70 for suture [9,19,20,22,26,30,46,51,53,75,76,78,83,, 9 for BPS [9,72,78,83,86,89,[141][142][143], 9 for Seal [9,30,61,74,78,103,[144][145][146], and 24 for APM [9,39,52,53,63,89,103,131,[147][148][149][150][151][152][153][154][155][156][157][158][159][160]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…4 A and B). Moreover, seven studies 60 , 62 67 , 69 , 71 reported the EWL at 6 months postoperatively, eight studies 62 , 63 , 65 , 67 71 reported the EWL at 12 months postoperatively, and only four studies 63 , 65 , 67 , 68 reported the EWL at 24 months postoperatively. The EWL at 6, 12, and 24 months postoperatively showed no statistical differences between the SLSG and CLSG (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Mittermair et al proposed limiting SPSG to patients with a BMI of < 45 kg/m 2 32 . Hiatal hernia, GERD, extremely high BMI (> 40 kg/m 2 ), and previous upper gastrointestinal surgery were suggested contraindications 9 , 33 . Our study set the recommended indication for SPSG as female patients with BMI ≤ 42 kg/m 2 and no history of upper abdominal surgery except for laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%